Corn Salad—Valerianella locusta (L.) Betcke - James M. Stephens (EDIS, 2003)
This document describes corn salad (Valerianella locusta), also known as lamb’s lettuce or fetticus, a mild-flavored leafy green used in salads or as a cooking green. It forms a rosette of spoon-shaped leaves and is sometimes blanched for tenderness. The plant is suited to Florida’s cool seasons and is cultivated similarly to lettuce or endive, with sowing recommended from September through May. Original publication date May 1994.